TANGGUNG JAWAB DIREKSI TERHADAP KERUGIAN PT BERDASARKAN DOKTRIN BUSINESS JUDGEMENT RULE - Sanditya Edi Kurniawan, I Made; Subha Karma Resen, Made Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
The paper entitled Responsibility of the Directors for damages Limited Liability Companies based on the doctrine of Business Judgment Rule. This paper uses analytical methods and normative uum approach. Director is an important organ in which the Board of Directors of a Limited Liability Company has a function and a very central role in the paradigm of limited liability company. Based on these functions when the Director makes a decision that hurt the company, based on the doctrine of Business judgment rule, directors of a company are not liable for damages arising from an act of decision-making, if the directors act in good faith and based on careful nature.
Keywords: Responsibility, Board of commissioners, Bankruptcy, Incorporated